In Vitro and In Vivo Effects of Endotoxin on Mouse Peritoneal Cells - Shands, J. W. (1974)
The in vitro effect of endotoxin (LPS) on unfractionated mouse peritoneal cells and cells fractionated into glass adherent and nonadherent populations was studied. LPS caused blast transformation and deoxyribonucleic acid synthesis in the nonadherent, nonphagocytic cells. There was no evidence of a mitogenic effect on macrophages. Instead, a cytotoxic effect was noted. When incubated with unfractionated peritoneal cells, LPS was still cytotoxic for macrophages, but the mitogenic effect for nonadherent cells was decreased or ablated. The intraperitoneal administration of LPS to mice resulted in an acute inflammatory response with a transient depletion of mononuclear cells. There was no stimulation of division of macrophages. Data were obtained which indicated that local cell division is an important factor in the normal turnover of peritoneal macrophages.